Analisis Faktor yang Memengaruhi Customer Loyalty dengan Mediasi Customer Satifaction pada Perbankan - Purwianti, Lily; Enjelica, Elvina (https://jurnal.binamandiri.ac.id/, 2024)
Currently, the banking world is experiencing very tight developments due to competitive rivalry between one bank and another. This research aims to analyze the influence of promotions, brand image, service quality, trust, and CRM on customer loyalty, which is mediated by customer satisfaction in the banking sector. This research has a population derived from the population of Batam City in 2020, namely 1,196,396 people. Based on the 1:10 method, a sample of 350 respondents was obtained. This research also uses quantitative methods using descriptive statistics with the results of promotions, brand image, service quality, trust, and customer relationship management, significantly influencing customer loyalty and customer satisfaction in the banking sector.